Synthesis of 2-substituted Furo[3,2-b]pyridines Under Pd/C-Cu Catalysis Assisted by Ultrasound: Their Evaluation as Potential Cytotoxic Agents - Laxmi, Dandamudi S.; Vardhini, Suryadevara V.; Guttikonda, Venkata R.; Rao, Mandava V.B.; Pal, Manojit (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Compounds containing furo[3,2-b]pyridine framework have shown interesting pharmacological properties, including anticancer activities. Though these compounds are generally synthesized via the heteroannulation processes involving acetylenic derivatives, some of them are complex. Objective: The study aimed to explore a series of 2-substituted furo[3,2-b]pyridines for their cytotoxic properties against cancer cell lines in vitro. Methods: We developed a convenient synthesis of 2-substituted furo[3,2-b]pyridines via sequential (i) C-C coupling followed by (ii) C-O bond-forming reactions in a single pot. The reactions were performed under ultrasound irradiation in the presence of Pd/C as an inexpensive, stable and widely used catalyst. A range of 2- substituted furo[3,2-b]pyridines were synthesized via coupling of 3-chloro-2-hydroxy pyridine with terminal alkynes in the presence of 10% Pd/C-CuI-PPh3-Et3N in EtOH. The in vitro evaluation of all these compounds was carried out against MDA-MB-231 and MCF-7 cell lines and subsequently against SIRT1. Results: The furo[3,2-b]pyridine derivative 3b showed encouraging growth inhibition of both MDAMB-231 and MCF-7 cell lines and inhibition of SIRT1. The compound 3b also showed apoptosis-inducing potential when tested against MCF-7 cells. Conclusion: The Pd/C-Cu catalysis under ultrasound accomplished a one-pot and direct access to 2-substituted furo[3,2-b]pyridine derivatives, some of which showed anticancer properties.
Keywords: catalysis